2019
DOI: 10.3390/met9111227
|View full text |Cite
|
Sign up to set email alerts
|

Refined Microstructure and Enhanced Hardness in Friction Stir-Welded AZ31 Magnesium Alloy Induced by Heat Pipe with Different Cooling Liquid

Abstract: The temperature field in welded plates has a significant influence on the microstructure and thereby their properties during friction stir welding (FSW). In this work, a self-designed heat pipe with different cooling liquid was applied in the FSW process for AZ31 magnesium alloy. The temperature fields, microstructures and properties of the welded joints were investigated. The peak temperatures and the durations of high temperature at both the advancing side and the retreating side decrease during the FSW proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 73 publications
0
3
0
Order By: Relevance
“…Compared with the base metal, the hardness across the whole welded joints declined under the FSW condition, the hardness distribution profile across the whole welded joint presents a "W" pattern, and the lowest hardness positions are presented between TMAZ and NZ (Figure 11a), which is consistent with outcomes in the Refs. [12,29,46]. Generally, the deformed metallic materials undergo the static recovery, recrystallization (T ≥ 0.5 T m , T m is the melting point) and other softening processes during annealing or heating, which results in a decrease in hardness [6,36].…”
Section: Microhardnessmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with the base metal, the hardness across the whole welded joints declined under the FSW condition, the hardness distribution profile across the whole welded joint presents a "W" pattern, and the lowest hardness positions are presented between TMAZ and NZ (Figure 11a), which is consistent with outcomes in the Refs. [12,29,46]. Generally, the deformed metallic materials undergo the static recovery, recrystallization (T ≥ 0.5 T m , T m is the melting point) and other softening processes during annealing or heating, which results in a decrease in hardness [6,36].…”
Section: Microhardnessmentioning
confidence: 99%
“…Antariksawan et al [27] conducted the straight heat pipe (SHP) in a water cooling tank (WCT) and found that the given SHP could transfer the heat from the WCT to a heat sink and prevent a continuous increase in the temperature of WCT. Furthermore, using a heat pipe to control the temperature in the FSW process was studied by Lu et al [28,29], where the heat pipe decreased the peak temperature during the FSW process and promoted the tensile property of welded AZ31 Mg alloy joints. Due to the highly-effective heat dissipation of the heat pipe, the excessive heat can be effectively taken away, which leads to better uniformity of the temperature field along the whole weld.…”
Section: Introductionmentioning
confidence: 99%
“…So far, there are a variety of surface modification methods for improving the surface properties of metallic materials, such as laser processing (Balla et al, 2010;Chai et al, 2017;Chai et al, 2018;Xiang et al, 2020), microarc oxidation (Wang et al, 2018b;Dehghanghadikolaei et al, 2019;Yang et al, 2020b), thermal spraying (Jaeggi et al, 2011;Chen et al, 2019a;Chen et al, 2019b), friction stir processing (Wang et al, 2015;Wang et al, 2017;Zhang et al, 2019c), ion implantation (Rautray et al, 2011;Qin et al, 2017), and so on. Among these methods, anodic oxidation is a costly method that applies an anodic potential on the metallic sample in the solution.…”
Section: Introductionmentioning
confidence: 99%